Tofacitinib for ulcerative colitis in Brazil: a multicenter observational study on effectiveness and safety - Parra, Rogério Serafim; de Sá Brito Fróes, Renata; Magro, Daniela Oliveira; da Costa Ferreira, Sandro; de Mello, Munique Kurtz; de Azevedo, Matheus Freitas Cardoso; Damião, Aderson Omar Mourão Cintra; de Sousa Carlos, Alexandre; Barros, Luísa Leite; de Miranda, Maria Luiza Queiroz; Vieira, Andrea; Sales, Marcos Paulo Moraes; et al. (Springer Nature, 2025)
Aim: To assess the real-life, long-term effectiveness and safety of tofacitinib in a large cohort of patients with refractory or difficult-to-treat ulcerative colitis (UC). Methods: This multicenter, retrospective, observational cohort study included patients with moderately to severely active UC who received tofacitinib for at least 8 weeks. Clinical remission and response, endoscopic response and remission, biochemical response and remission, steroid-free clinical remission, primary and secondary loss of response, drug discontinuation, the need for dose optimization, the need for colectomy, and adverse events were evaluated over up to 30 months. Results: We included 127 patients with UC, with a mean age of 40.3 ± 14.2 years; 58.2% were male, 75.6% had pancolitis, and 79.5% had previously failed at least one biological therapy, predominantly anti-TNF agents (70.1%). Clinical remission was observed in 31.5% of patients at weeks 12–16, 46.5% at 26 ± 4 weeks, and 37.0% at 1 year. Steroid-free clinical remission was achieved in 28.6%, 44.8%, and 37.1% of patients at the same time points, respectively. Biochemical remission was achieved in 33.6% of patients at 26 ± 4 weeks and 29.3% at 1 year. Endoscopic response and endoscopic remission within 1 year were observed in 46.0% and 15.3% of patients, respectively. Ten patients (7.9%) required colectomy, and 13 patients (10.2%) required hospitalization, all of whom had been previously exposed to biologics. The colectomy rate was significantly greater in patients with serum albumin levels ≤ 3.5 g/dL (21.4% vs. 4.1%, p = 0.013). Conclusion: In this large, long-term real-world study involving patients with predominantly biologically refractory UC, tofacitinib effectively induced clinical remission and endoscopic improvement and prevented colectomy for more than 30 months, with a favorable safety profile. Notably, baseline hypoalbuminemia was associated with higher colectomy rates.
Keywords: Inflammatory bowel disease; Jak inhibitors; Tofacitinib; Real-world; Ulcerative colitis